Time in Care for Older People Living in Nursing Homes - K. B. E. Thorsell; B. M. Nordström; L. Fagerström; B. V. Sivberg (Nursing Research and Practice)
In order to measure actual care needs in relation to resources required to fulfill these needs, an instrument (Time in Care) with which to evaluate care needs and determine the time needed for various care activities has been developed with the aim of assessing nursing intensity in municipal care for older people. Interreliability (ICC=0.854) of time measurements (n=10'546) of 32 nursing activities in relation to evaluated care levels in two nursing homes (staff n=81) has been determined. Nursing intensity for both periods at the two nursing homes comprised on average a direct care time of 75 (45%) and 101 (42%) minutes, respectively. Work time was measured according to actual schedule (462 hours per nursing home during two weeks). Given that the need for care was high, one must further investigate if the quality of care the recipients received was sufficiently addressed.